2008
DOI: 10.1080/13557850802009488
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation, social support, and quality of life for Korean immigrant breast and gynecological cancer survivors

Abstract: The evidence that acculturation influences QOL through social support for Korean immigrant cancer survivors should serve as a rationale for developing psychosocial interventions that enhance immigrant cancer survivors' social participation and adjustment in the unfamiliar US environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
2
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 59 publications
(49 reference statements)
3
38
2
5
Order By: Relevance
“…For cancer survivors specifically, fear of recurrence and distress related to physical compromise are other psychological effects [36][37][38]. Additionally, several studies have documented that psychological well-being influenced PQOL through social support [39][40][41][42].…”
Section: The Contextual Model Of Hrqolmentioning
confidence: 99%
See 1 more Smart Citation
“…For cancer survivors specifically, fear of recurrence and distress related to physical compromise are other psychological effects [36][37][38]. Additionally, several studies have documented that psychological well-being influenced PQOL through social support [39][40][41][42].…”
Section: The Contextual Model Of Hrqolmentioning
confidence: 99%
“…Moreover, Latina-Americans perceive the doctor-patient relationship as an important factor of obtaining quality medical care, but they have some concerns with trust in their health care providers [100]. Given that financial, linguistic, institutional, and social status factors limit access to and use of health services as well as patient satisfaction, facilitating the receipt of quality medical and supportive care may be particularly important for underserved populations [42,[101][102][103][104].…”
Section: Demographic Informationmentioning
confidence: 99%
“…Higher levels of acculturation (reduced language barriers) were positively related to their level of QOL. High language barriers were related to lower social network involvement (Kim et al, 2006; Lim, Yi, & Zebrack, 2008). Longer length of stay in U.S. was positively associated with larger social network size, greater social involvement, and fewer language barriers (Lim et al, 2008).…”
Section: Presentation Of Findingsmentioning
confidence: 99%
“…Lim (2014) also found that breast cancer survivors who used more social support from extended family, friends, and neighbors, or sought more spiritual support had better mental-related QOL. Furthermore, those with positive social network structures (i.e., larger network size, more diverse networks, and greater network involvement) had better emotional support and QOL (Lim et al, 2008). These studies all suggest that social support is a key factor related to Korean American cancer survivors’ QOL and that social network size and network involvement have a positive influence on emotional support.…”
Section: Presentation Of Findingsmentioning
confidence: 99%
“…Acculturation has been thought of as unidimensional (Abraido-Lanza, 2006)—i.e., as assimilation to the mainstream culture—or bidimensional, which acknowledges immigrants' abilities to hold onto their original beliefs, while assimilating to the new culture (Miller, 2010). Regardless of framework, two variables in particular— immigrants' length of stay in the U.S. and language use (Barry, 2001; Kuo & Roysircar, 2004; Lim, Ye, & Zebrack, 2008)—have been viewed as key variables in capturing acculturative processes of Asians to U.S. culture. These two variables have been found to strongly predict the acculturative process in studies of Chinese Canadians (Kuo and Roysircar 2004) and Asian Americans (Sodowsky & Plake, 1992), and also have predicted positive psychosocial outcomes among Korean immigrants diagnosed with cancer (Lim et al, 2008).…”
mentioning
confidence: 99%